Arahan Penataan Bangunan dan Lingkungan pada Kawasan Keraton Pakunegara Tayan Kabupaten Sanggau Kalimantan Barat - Dian Perwita Sari; M Ridha Alhamdani (TATALOKA, 2020)
The area of the Palace of Pakunegara Tayan, Sanggau Regency, West Kalimantan, currently requires arrangement in the form of directions and guidelines of buildings and environment for the region so it could be ordering. The uncontrolled and rapid development reduces the carrying capacity of the environment, the building's growth does not follow the applicable rules are the main factors for regional management. This study used descriptive qualitative research methods. The descriptive qualitative method aims to describe the current situation to identify the existing conditions of the Keraton Pakunegara Tayan area. Besides, this approach used to examine cause and effect through the identification of symptoms from existing problems and from the analysis, the regional arrangement concept scheme made. The results of this study obtain two concepts of structuring the Pakunegara Tayan Palace Area, they are adaptive development and integrated development, where each concept developed and elaborated with urban design elements so can provide direction for the physical manifestation of the Urban Area, which refers to the Spatial Plan (RTR) as well as local socio-cultural norms/norms, to create environment well planned, orderly, safe, comfortable, harmonious, productive and sustainable in surroundings of the Keraton Pakunegara Tayan area.